2021
DOI: 10.1155/2021/4650245
|View full text |Cite
|
Sign up to set email alerts
|

Overview of In-Hospital 3D Printing and Practical Applications in Hand Surgery

Abstract: Three-dimensional (3D) printing is spreading in hand surgery. There is an increasing number of practical applications like the training of junior hand surgeons, patient education, preoperative planning, and 3D printing of customized casts, customized surgical guides, implants, and prostheses. Some high-quality studies highlight the value for surgeons, but there is still a lack of high-level evidence for improved clinical endpoints and hence actual impact on the patient’s outcome. This article provides an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…Новые технологии ВВЕДЕНИЕ За последнее десятилетие технология трехмерной печати получила развитие в медицине, она открывает новые перспективы в научных исследованиях, обучении персонала и в индивидуальном подходе к лечению, позволяя повысить его эффективность [1][2][3]. По мнению специалистов, в хирургии трехмерную печать можно использовать для создания геометрически сложных и высокодетализированных персонализированных конструкций и их одноразового изготовления, для предоперационного планирования, проектирования ортопедических изделий и протезирования в соответствии с конкретными требованиями хирурга и пациента [3][4][5][6], для создания вспомогательных средств, адаптированных для конкретного пациента, для интраоперационного использования, создания аппаратных средств и индивидуальных устройств, протезов для имплантации, быстрого создания прототипов хирургически имплантируемых изделий, а также приложений для обучения стажеров [7][8][9][10]. Преимуществом технологии является то, что индивидуальные имплантаты и слепки могут быть изготовлены в соответствии с анатомией конкретного человека [9,11].…”
Section: гений ортопедии 2024;30(3)unclassified
“…Новые технологии ВВЕДЕНИЕ За последнее десятилетие технология трехмерной печати получила развитие в медицине, она открывает новые перспективы в научных исследованиях, обучении персонала и в индивидуальном подходе к лечению, позволяя повысить его эффективность [1][2][3]. По мнению специалистов, в хирургии трехмерную печать можно использовать для создания геометрически сложных и высокодетализированных персонализированных конструкций и их одноразового изготовления, для предоперационного планирования, проектирования ортопедических изделий и протезирования в соответствии с конкретными требованиями хирурга и пациента [3][4][5][6], для создания вспомогательных средств, адаптированных для конкретного пациента, для интраоперационного использования, создания аппаратных средств и индивидуальных устройств, протезов для имплантации, быстрого создания прототипов хирургически имплантируемых изделий, а также приложений для обучения стажеров [7][8][9][10]. Преимуществом технологии является то, что индивидуальные имплантаты и слепки могут быть изготовлены в соответствии с анатомией конкретного человека [9,11].…”
Section: гений ортопедии 2024;30(3)unclassified
“…Nevertheless, studies have shown that surgeons benefit from 3-D technology when dealing with complex cases (Meyer-Szary et al., 2022) and that the use of 3-D models contributes to patient education (Bizzotto et al., 2015; Samaila et al., 2020). There have been continuous efforts to validate applications of this technology as well as its cost effectiveness (Keller et al., 2021; Samaila et al., 2020). Cost effectiveness has been successfully demonstrated in other fields (Chamo et al., 2020); assistance to surgeons, especially with complex cases, should result in shorter operating times and fewer indirect costs.…”
Section: The Current Role Of 3-d Printing In Upper Extremity Surgerymentioning
confidence: 99%
“…The emergence of three-dimensional (3D) technology offers the potential for personalized splint design, which may address the drawbacks associated with conventional treatment. [6][7][8][9][10][11][12] To achieve this, commercially available 3D camera systems are utilized to capture patient extremities, generating 3D models for patient specific splint design. [10,13,14] design.…”
Section: Introductionmentioning
confidence: 99%